Risk Factors for Preeclamsia - Harnanik Nawangsari; Raudhatul Munawarah; Rosita Syaripah (International Forum of Researchers and Lecturers, 2025)
Preeclampsia is a severe pregnancy complication characterized by hypertension and signs of organ damage, with a multifactorial etiology involving maternal, genetic, and environmental interactions. This study aims to analyze determinants contributing to the occurrence of preeclampsia through a comprehensive literature review. The research method involved an in-depth analysis of 15 scientific journals, consisting of 8 national publications from Google Scholar and 7 international publications from PubMed, selected based on relevance, credibility, and publication date. Data from these sources were synthesized to identify common risk factors, biological mechanisms, and preventive measures. The findings indicate that the primary risk factors for preeclampsia include a history of chronic hypertension, obesity, gestational diabetes, nulliparity (first pregnancy), and a family history of preeclampsia. Nutritional deficiencies, particularly low calcium and vitamin D intake, are also significantly associated with increased risk. Furthermore, immunological factors such as abnormal maternal immune tolerance, as well as placental dysfunction leading to poor perfusion, play a crucial role in the pathogenesis of preeclampsia. The interplay between these factors suggests that preeclampsia is not caused by a single mechanism, but rather by a complex network of physiological, metabolic, and genetic influences. This complexity underscores the importance of early risk factor identification and intervention strategies during antenatal care. Preventive efforts may include nutritional supplementation, weight management, blood pressure monitoring, and targeted medical interventions for high-risk individuals. In conclusion, preeclampsia remains a significant contributor to maternal and perinatal morbidity and mortality worldwide. Understanding its determinants enables healthcare providers to implement timely preventive measures and reduce its negative impacts on both mother and fetus. Further research is warranted to elucidate the precise mechanisms underlying these determinants, potentially paving the way for more effective prevention and treatment strategies.